O ensino religioso nas escolas públicas: uma violação da laicidade do Estado? - Polidoro, Lurdes Fátima (2010)
The object of this study is to analyze the controversy between the design of which promote and defend the separation of church and state, as well as the neutrality of the state in relation to religious education. Based in a the anthropological vision, it is understood that the Religious Education can help in the development and promotion of human being in all its dimensions, enabling integration and coexistence among followers of different religious strands.. Therefore, it is necessary to fight so that there is a genuine religious education within the system of public education. This work also takes into account the situation of contemporary secular society in order to understand, then, the role of religious education in a secular state. The hypothesis is that the Religious Education, in Public School, does not violate the secular state. We conclude that the State, by requiring the discipline of Religious Education for public schools elementary school, is not violating the constitutional principle of secularism of the state. The State must guarantee the Religious Education as a right of citizens and students, banning any kind of proselytizing